2012
DOI: 10.1111/j.1364-3703.2012.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel virulence‐related gene nlxA in the lipopolysaccharide cluster of Xanthomonas citri ssp. citri is involved in the production of lipopolysaccharide and extracellular polysaccharide, motility, biofilm formation and stress resistance

Abstract: SUMMARY Lipopolysaccharide (LPS) is an important virulence factor of Xanthomonas citri ssp. citri, the causative agent of citrus canker disease. In this research, a novel gene, designated as nlxA (novel LPS cluster gene of X. citri ssp. citri), in the LPS cluster of X. citri ssp. citri 306, was characterized. Our results indicate that nlxA is required for O‐polysaccharide biosynthesis by encoding a putative rhamnosyltransferase. This is supported by several lines of evidence: (i) NlxA shares 40.14% identity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 49 publications
(75 reference statements)
0
26
0
1
Order By: Relevance
“…[42][43][44] The genes involved in quorum sensing, phosphodiesterase, polyphosphate kinase, and LPS synthesis all contribute to biofilm formation, which plays a role in motility, stress sensing, and changes in colony morphology. 15,27,38,[45][46][47] Because the colony morphology of B. pseudomallei was altered after growth in a soil environment, the morphology related characteristics, such as flagellin expression, concentration of C 14:0 3-OH FA (a LPS indicator) and biofilm formation, which are also virulence determinants, might be similarly changed after growth in the environment. The C 14:0 2-OH FA has been documented to be a feature that distinguishes virulent B. pseudomallei strains from non-virulent Burkholderia thailandensis strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44] The genes involved in quorum sensing, phosphodiesterase, polyphosphate kinase, and LPS synthesis all contribute to biofilm formation, which plays a role in motility, stress sensing, and changes in colony morphology. 15,27,38,[45][46][47] Because the colony morphology of B. pseudomallei was altered after growth in a soil environment, the morphology related characteristics, such as flagellin expression, concentration of C 14:0 3-OH FA (a LPS indicator) and biofilm formation, which are also virulence determinants, might be similarly changed after growth in the environment. The C 14:0 2-OH FA has been documented to be a feature that distinguishes virulent B. pseudomallei strains from non-virulent Burkholderia thailandensis strains.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] The expression of one or more of these virulence determinants is associated with changes in bacterial colony morphology. [13][14][15][16] In B. pseudomallei, wrinkled and dry colonies are commonly observed in human isolates, and these morphologies are associated with the degree of virulence in BALB/c mice. Smooth and mucoid morphologies are more common to soil isolates and are less virulent.…”
Section: Introductionmentioning
confidence: 99%
“…We identified a gene region involved in LPS biosynthesis (J151_03781-J151_03787, equal to XAC3596-XAC3601, totally 7 genes, nlxA is recently determined in the intergenic region of XAC3597 and XAC3598; Yan et al, 2012) in XacA that was highly variable from that of XacA w and XacA*, but the upstream and downstream genes were conserved (Figure 3a). Three of the genes in this region, nlxA, wzt and wzm, are 'metabolism' genes.…”
Section: Genomic Features Of Citrus Canker-causing Xac Strainsmentioning
confidence: 99%
“…Positive selection for evolution of Xac Y Zhang et al genes in this region, such as wxacO, rfbC, nlxA and wzt, have been demonstrated to be involved in O-antigen synthesis and transport and be associated with biofilm formation on the host and contribute to virulence in XacA (Casabuono et al, 2011;Li and Wang, 2011;Petrocelli et al, 2012;Yan et al, 2012). Among the three components, lipid A, core and O-antigen that are composed of the entire Xac LPS, the O-antigen region is probably the most important for host basal response during citrus-pathogen interaction (Casabuono et al, 2011).…”
Section: Genomic Features Of Citrus Canker-causing Xac Strainsmentioning
confidence: 99%
“…In X. citri, LPS mutants that were reduced in virulence showed poor biofilm formation, providing one plausible connection (18). However, progress has otherwise been rather limited, largely because mutations that cause LPS defects are often pleiotropic, altering other components or properties important for pathogenesis, such as extracellular polysaccharide (EPS), or, more generally, reducing resistance to environmental stresses (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%